Physical Education Teacher Perspective On Kurikulum Merdeka and Sport Education Model: A Rasch Model Analysis - Lutfi Nur; Teten Hidayat; Arief Abdul Malik (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Changes and implementations of the new curriculum require a careful preparation and information about the Independent Curriculum, known as Kurikulum Merdeka. The learning model used needs to be explored as an illustration of teacher understanding. This study aimed to examine teacher perspectives regarding their understanding of the Kurikulum Merdeka and the Sport Education Learning Model. The cross-sectional survey method was used to collect data. Data were collected using Google Form filled by 74 teachers. The research instrument was in a Likert scale form and consisted of 30 questions focused on exploring teacher understanding of the Kurikulum Merdeka, the Sport Education (SEM) Learning Model, the SEM Phases/Syntax, and the roles existing in the implementation of the SEM Model and the importance of understanding curriculum and learning models in school. Then, 15 open-ended questions related to models often used by teachers, training expectations to follow, and obstacles experienced during learning at school were given. The research data were processed using Winsteps 5.2.3 software. The Rasch Model analysis was used to analyze the instruments made and the results of the teacher understanding perspective. The results showed that the instrument was valid for use. Related to the results of the teacher perspective, 48.6% of physical education teachers had an understanding and belief in the importance of the Kurikulum Merdeka and the SEM model in elementary schools at a high level. Meanwhile, 12. 2% were at the moderate level and 39.2% were at the low level. These findings can be used as a reflection related to the teacher understanding of the Kurikulum Merdeka and the Sport Education Learning Model and as a reference in arranging training needed for Physical Education teachers in the field.